Representasi Krisis Identitas Gender Pasca Operasi Kelamin (Studi Tentang Detransitioner di Kanal Youtube Blaire White) - Fahrudin, Atef; Wulandari, Ajeng Ayu (CommLine, 2025)
This study examines the representation of post-surgical gender identity crisis in Blaire White's YouTube channel through the narrative of detransitioner "Shape Shifter." Using qualitative methodology with thematic analysis and phenomenological approach, this research applies Erik Erikson's identity crisis theory and Stuart Hall's representation theory to understand how gender identity crisis is constructed and communicated in digital media spaces. The analysis reveals five major themes: post-operative identity crisis (30%), medical complications (25%), medical system criticism (20%), social impact (15%), and acceptance and learning (10%). The findings indicate that detransition represents a non-linear process involving eight complex stages, from gender dysphoria to becoming an activist. Medical concerns dominate with 25 occurrences, followed by sadness (18) and regret (15), demonstrating that detransition experience is characterized by loss-oriented coping rather than restoration-oriented coping. Linguistic analysis shows medical terminology dominance (90%) and high affective saturation (85%), reflecting profound medicalization of experience in autobiographical narrative construction. The research concludes that post-surgical gender identity crisis requires holistic gender-affirming care approaches considering psychosocial dimensions and long-term support systems. Digital media representation through platforms like YouTube plays a crucial role in shaping public understanding of gender identity through complex negotiations between medical discourse, emotional expression, and identity formation processes.